The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1111/opo.12939
|View full text |Cite
|
Sign up to set email alerts
|

Low‐intensity, long‐wavelength red light slows the progression of myopia in children: an Eastern China‐based cohort

Abstract: Myopia is prevalent worldwide, particularly in East and Southeast Asia. Recent studies have suggested that the spectral composition of ambient lighting in uences refractive development, especially in humans. We aimed to determine the effect of 650-nm single-wavelength red light on the inhibition of myopia progression in children. In this retrospective cohort study, 105 myopic children (spherical equivalent refractive error [SER], -6.75 to -1.00 dioptres (D)) aged from 4 to 14 years old were retrospectively rev… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
79
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(97 citation statements)
references
References 53 publications
5
79
3
Order By: Relevance
“… 16 18 This study result aligns with previous findings, with AL changes of −0.01 mm at 6 months and 0.08 mm at 1 year in the RLRL group. Refraction changes were also similar, with SER changes of 0.29 D at 6 months and 0.05 D at 6 to 12 months, similar to the results for the studies by Jiang et al 16 (−0.03 D and 0.20 D, respectively) and Zhou et al 17 (0.19 D at 6 months). The continuity of such promising results reinforces the notion that RLRL is an effective treatment for AL and refraction in myopes.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“… 16 18 This study result aligns with previous findings, with AL changes of −0.01 mm at 6 months and 0.08 mm at 1 year in the RLRL group. Refraction changes were also similar, with SER changes of 0.29 D at 6 months and 0.05 D at 6 to 12 months, similar to the results for the studies by Jiang et al 16 (−0.03 D and 0.20 D, respectively) and Zhou et al 17 (0.19 D at 6 months). The continuity of such promising results reinforces the notion that RLRL is an effective treatment for AL and refraction in myopes.…”
Section: Discussionsupporting
confidence: 88%
“… 16 A similar effect was observed after a 9-month follow-up in a retrospective study. 17 When Xiong et al 18 compared RLRL with orthokeratology, a more profound effect on axial length (AL) control was evident after RLRL treatment for 6 months. In these studies, a 650-nm, single-wavelength red light was used, and the protective effect appears to be associated with an increase in choroidal thickness.…”
Section: Introductionmentioning
confidence: 99%
“…Five had increases in AL that were compatible with coordinated growth (0.023 mm ≤ ΔAL ≤ 0.052 mm) ( Table 6 , participants 2–6), and one presented with annual AL shortening (ΔAL = −0.062). The decrease in AL in either season observed in some participants and throughout the year for this one participant could be indicative of axial elongation being reversible—as previously reported in animals 67 and humans (children, 68 72 as well as adolescents and young adults 13 , 31 , 73 , 74 ). Nonetheless, as reported from animal studies, 67 the amount of choroidal thickening does not equal the amount of eye shortening.…”
Section: Discussionsupporting
confidence: 81%
“…The 630 nm light used by Hung et al [ 117 ] and the 624 ± 10 nm light used by Gawne et al [ 118 ] showed significant effects on myopia control in rhesus monkeys and tree shrews. Recently, He et al found that repeated low-level red light (RLRL) therapy (650 nm, 1600 lx) could effectively improve the progression of myopia in children aged 8–13 years [ 119 ], and low-intensity, long-wavelength red light therapy (LLRT, 635 nm) inhibited myopia progression in children in an Eastern China-based cohort [ 120 ]. The effect of red light on myopia has recently gained more attention (Table 1 ).…”
Section: Controversies and Considerationsmentioning
confidence: 99%